2013
DOI: 10.1080/00222895.2012.760512
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Differs But Not Reaction Time When Intercepting a 3D Versus 2D Videoed Opponent

Abstract: The authors aimed to identify differences in (a) visual search and (b) reaction time when athletes sidestepped to intercept 2D versus 3D videoed opponents. They hypothesized that participants would (a) fixate on different parts of the opponent's body and (b) react quicker when responding to the 3D versus 2D opponent due to the added depth cues. A customized integrated stereoscopic system projected the video stimuli and synchronously recorded the gaze and motor behaviors of 10 men when they responded to two- (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Additionally, Yang and Lee (2016) showed that coaches' instructions concerning the defensive position of handball goalkeepers could benefit from the analysis of real videotaped matches. On the other hand, the impoverishment of informational content of 2D visual scenarios was found to be the major drawback of video-based methods because attentional focus and reaction time are also influenced by depth (Lee et al, 2013). With these limitations, players may not be able to pick up key information, such as parallax, and may not be able to interact with the system realistically (Aglioti, Cesari, Romani, & Urgesi, 2008).…”
Section: Limitations With Video-and Vr-based Systemsmentioning
confidence: 99%
“…Additionally, Yang and Lee (2016) showed that coaches' instructions concerning the defensive position of handball goalkeepers could benefit from the analysis of real videotaped matches. On the other hand, the impoverishment of informational content of 2D visual scenarios was found to be the major drawback of video-based methods because attentional focus and reaction time are also influenced by depth (Lee et al, 2013). With these limitations, players may not be able to pick up key information, such as parallax, and may not be able to interact with the system realistically (Aglioti, Cesari, Romani, & Urgesi, 2008).…”
Section: Limitations With Video-and Vr-based Systemsmentioning
confidence: 99%
“…In terms of our behavioural results, we found what was expected -participants lost more against the hard opponent, won more against the easy opponent, and had equivalent outcomes against the average opponent. Interestingly, we did not find a difference in response time for participants moves against any of the three opponents -thus a speed -accuracy tradeoff was not observed [33,34]. Further, we did not find any difference in response selection in relation to opponent ability (see Figure 3).…”
Section: Discussionmentioning
confidence: 48%
“…[8] who developed a series of S3D projections featuring semi-realistic game scenarios for investigating the associations between evasive side-stepping and the risk of anterior cruciate ligament injuries in soccer players [9] . Compared with two-dimensional videos of the same scenes, previous research using eye-tracking [10] and functional brain imaging [11] , [12] , [13] , [14] suggest that the additional depth cues present in S3D videos significantly modulates both dorsal and ventral visual information processing streams that subserve vision-for-action and vision-for-perception [15] . To the best of the author's knowledge, the techniques and technology have yet been used beyond research in sport.…”
Section: *Methods Detailsmentioning
confidence: 97%
“…To capitalize on the dual-purpose S3D stimuli, it was essential to set a common perturbation zone (i.e., unknown to the participants) for both the verbal-perceptual and steering-avoidance tasks, where the participants would approximately be at the same distance in front of the S3D person when the change in direction was initiated. The temporal precision required for both tasks could be achieved with the use of customised timing gates and an interface unit [10] that not only aid in triggering the video playback for both tasks ( Fig. 1 B and C), but also monitor and account for any inter-participant differences in walking velocity in the steering-avoidance task when positioned appropriately.…”
Section: *Methods Detailsmentioning
confidence: 99%